Peace and Order Program by the Barangay Gulod Officials in Novaliches Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This survey research was conducted to find out the peace and order program by the BarangayGulod officials in Novaliches, Quezon City, in BSCRIM at Bestlink College of the Philippines.Questions were formulated to guide the study. The population of the study consists ofbarangay officials, law enforcers, and the community of Barangay Gulod. Through the processof purposive sampling, a total number of 50 constituents of Barangay Gulod were selected toparticipate in the study. The major instrument used for gathering data was a surveyquestionnaire. The data gathered were analyzed through the use of percentages andweighted mean. Based on the analysis, it was discovered that most of the respondents areafraid to open up to other members of the family.Through the process of this paper, the researcher is able to see the real problem that occurredin each situation of respondents there is a need of Increasing funding can be a potentialsolution for meeting the needs of people in a certain area, but it may not always be the bestsolution. It is important to consider the root causes of the issues faced by the community andto identify the most effective and sustainable ways to address them.In some cases, adding more funds to create more programs may be appropriate, particularly ifthe programs are evidence-based and have a proven track record of success. However, it isalso important to ensure that the programs are tailored to the specific needs of the communityand that they are implemented effectively.
Keywords: Criminology